Identifikasi Glibenklamid Pada Jamu Kencing Manis Yang Beredar di Medan Johor - Andriani, Vina; Sembiring , Novitaria Br; Bangar, Roy Indrianto (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: The increasing use of traditional herbal medicine (jamu) for diabetes treatment in the community has been accompanied by a rise in counterfeiting practices, particularly through the addition of synthetic drugs such as glibenclamide (C₂₃H₂₈ClN₃O₅S) to enhance efficacy and sales. This poses potential health risks, thereby necessitating strict monitoring of circulating herbal products. Objective: This study aims to identify the presence of glibenclamide in three samples of antidiabetic jamu available in Medan Johor using Fourier-Transform Infrared Spectroscopy (FTIR). Method: Identification was carried out by comparing the FTIR spectra of the samples (wavenumber range 650–4000 cm⁻¹) with that of the BPFI glibenclamide standard. The characteristic functional groups of glibenclamide used as reference were 3369.5 cm⁻¹ (Amide N–H Stretching), 1714.6 cm⁻¹ (C=O Stretching), and 1155.5 cm⁻¹ (S=O Stretching). Results: The analysis showed that none of the three samples (A2, A3, A4) exhibited absorption peaks corresponding to the critical wavenumbers of glibenclamide. Therefore, the tested samples were declared free from the pharmaceutical chemical substance (PCS) glibenclamide. Conclusion: These findings indicate that the three jamu products are safe for consumption when used as directed. However, routine surveillance by the National Agency of Drug and Food Control (BPOM) remains essential to ensure the safety of herbal products on the market. Further studies using more sensitive methods such as UV-Vis spectrophotometry are recommended to verify these results.